2014
DOI: 10.1515/cjal-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

From Learning English to Learning in English: A Comparative Study of the Impact of Learning Contexts upon Chinese EFL Learners’ Strategy Use

Abstract: The past three decades have witnessed a proliferation of research on Chinese English as a foreign language (EFL) learners' use of learning strategies, but little has been examined about the potential influence of learning contexts upon their strategic engagement. This paper reports on the findings of an investigation of the impact of learning contexts upon the use of learning strategies of two cohorts of EFL learners in China. Both cohorts were non-English majors, one from a university where English is the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 15 publications
5
22
0
Order By: Relevance
“…The study explored the structure of the SILL and its groups of items, which reflect the groups of strategies used by ESP learners in the researched context in Slovenia. With respect to the aggregated group results of the survey, compensation, metacognitive, and cognitive strategy groups had the three highest group means, followed by the social and memory groups, while the affective group of strategies had the lowest mean, which is comparable to the findings regarding Chinese students in the research of Li (2014). Although compensation strategies might be used to compensate for a lower level of language knowledge, the participants in Lai's (2009) research also reported using compensation strategies most frequently (and affective strategies least frequently).…”
Section: Structure Of the Sill And The Impact Of The Adapted Modelsupporting
confidence: 75%
See 1 more Smart Citation
“…The study explored the structure of the SILL and its groups of items, which reflect the groups of strategies used by ESP learners in the researched context in Slovenia. With respect to the aggregated group results of the survey, compensation, metacognitive, and cognitive strategy groups had the three highest group means, followed by the social and memory groups, while the affective group of strategies had the lowest mean, which is comparable to the findings regarding Chinese students in the research of Li (2014). Although compensation strategies might be used to compensate for a lower level of language knowledge, the participants in Lai's (2009) research also reported using compensation strategies most frequently (and affective strategies least frequently).…”
Section: Structure Of the Sill And The Impact Of The Adapted Modelsupporting
confidence: 75%
“…We used the SILL questionnaire in English in spite of the fact that some researchers Vol. 7(2)(2019): have warned about wording problems (Li, 2014) and other limitations, such as students' inability to remember accurately how and when SLLS were usedand a lack of self-awareness when filling in a self-report questionnaire (Griffiths, 2003). On the other hand, translation might cause some other issues of understanding and interpretation.…”
Section: Instrumentmentioning
confidence: 99%
“…Research (Jiang & Smith, 2009;Li, 2014) on Chinese EFL learners' strategies showed that emotion and satiation strategies (affective and social strategies in Oxford's, 1990, terms) were least applied by Chinese learners in a traditional teacher-fronted classroom. Given that one of the aims of this research is to identify differences of Chinese EFL learners' strategy use between a teacher-fronted classroom and a mobile-technology-assisted learning setting, emotion and satiation control strategies in Dörnyei's (2005) framework were left out of the questionnaire item design.…”
Section: Methodology and Data Collectionmentioning
confidence: 99%
“…Another strand of research on learning strategies in traditional language learning contexts is largely focused on learners' language output and vocabulary acquisition (Seker, 2016;Tseng & Schmitt, 2008;Zhang, Lin, Zhang & Choi, 2017). Cognitive and compensation (environmental control) strategies have been found to be the most frequently used strategies in an examination-oriented and teacher-led learning environment (Dmitrenko, 2017;Li, 2014). In research on learning strategies supported by technologies, the usefulness of different technologies has been consistently reported (e.g.…”
Section: Learning Strategiesmentioning
confidence: 99%
“…Given the differences in demotivation among EFL learners of different academic fields, teachers and curriculum designers are suggested to take academic fields into account while designing and developing English class to students of different majors. As for the deficiency of effective learning strategies among the learners, a strategy-embedded instruction is thus necessary to be incorporated into English language curriculum (Li, 2014c).…”
Section: Resultsmentioning
confidence: 99%